2019
DOI: 10.1111/jfpp.14272
|View full text |Cite
|
Sign up to set email alerts
|

Quality parameters, antioxidant activity, and sensory acceptability of mixed jams of rose petals and apple

Abstract: The objective was to develop mixed jams of rose petals and apple and to evaluate the physicochemical and sensory characteristics. Four formulations were made varying the concentration of rose petals (10%, 15%, 20%, and 25%). The higher the concentration of rose petals, the higher the phenolics and the antioxidant activity of the jams. A high correlation was observed between the total phenolics and antioxidant activity. No differences were observed among the jams to the L* value, hue angle, chroma, soluble soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…No significant difference ( p < 0.05) in pH values was found in the treated groups compared to the control one for all days of storage (from 4.78 to 5.06). Slight differences were found by Moreira et al (2019), who reported pH values of 3.9 and 4.04 in mixed jams of rose petals and apple, respectively. This can be explained by the addition of citric acid by these authors, which was not done in the current study.…”
Section: Resultsmentioning
confidence: 93%
“…No significant difference ( p < 0.05) in pH values was found in the treated groups compared to the control one for all days of storage (from 4.78 to 5.06). Slight differences were found by Moreira et al (2019), who reported pH values of 3.9 and 4.04 in mixed jams of rose petals and apple, respectively. This can be explained by the addition of citric acid by these authors, which was not done in the current study.…”
Section: Resultsmentioning
confidence: 93%
“…Roses are rich in vitamins, amino acids, and many functional components that benefit health conditions such as inflammation, hematemesis, and diarrhea. At the same time, rose possesses cosmetic and skin-moisturizing properties, can help reduce pain, functions as an aromatic deodorant, and invigorates the spleen (Cheng & Zhen, 2017;D'Angiolillo et al, 2018;Hegde et al, 2022;Nadpal et al, 2018). In food industry, rose petals are often used for jam, syrup, sherbet, creams for cakes, marmalade, vinegar, wine, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Rose jam is fermented under conditions that are mainly produced by inherent processes involving complex communities of microorganisms. The therapeutic properties of rose jam include stomachic and a tonic for the heart, stomach, and uterus, moisturizing the skin, and promotes blood circulation and metabolism (Li et al, 2022; Moreira et al, 2019; Youssef & Mousa, 2012). Rose jam is a popular and early staple in pastries, fillings, and dishes.…”
Section: Introductionmentioning
confidence: 99%
“…R. rugosa petals, recognized for their high polyphenol content, are a valuable raw material for human dietary supplements [ 46 ]. Thus, different experimental designs have been used to find the optimal fermentation conditions to produce fermented R. rugosa ‘Mohong’(FRM), aiming to generate a high polyphenol content and enhance its various biological effects.…”
Section: Introductionmentioning
confidence: 99%